Robotic systems for handling and assembly - Schèutz, Daniel; Wahl, Friedrich M. 1948-.; SpringerLink (Online service). (Berlin Heidelberg Springer, 2011)
Although parallel robots are known to offer many advantages with respect to accuracy, dynamics, and stiffness, major breakthroughs in industrial applications have not yet taken place. This is due to a knowledge gap preventing fast and precise execution of industrial handling and assembly tasks. This book focuses on the design, modeling, and control of innovative parallel structures as well as the integration of novel machine elements. Special attention is paid to the integration of active components into lightweight links and passive joints. In addition, new control concepts are introduced to  minimize structural vibrations. Although the optimization of robot systems itself allows a reduction of cycle times, these can be further decreased by improved path planning, robot programming, and automated assembly planning concepts described by 25 contributions within this book. The content of this volume is subdivided into four main parts dealing with Modeling and Design, System Implementation, Control and Programming as well as Adaptronics and Components. This book is aimed at researchers and postgraduates working in the field of parallel robots as well as practicing engineers dealing with industrial robot development and robotic applications.
Part I Kinematics, Dynamics - Modeling and Design -- Part II Implemented Systems -- Part III Control and Programming.
Electronic reproduction.
Keywords: Parallel kinematic machines; Electronic books